2018
DOI: 10.3390/vibration1010012
|View full text |Cite
|
Sign up to set email alerts
|

Improved Modelling of a Nonlinear Parametrically Excited System with Electromagnetic Excitation

Abstract: In this work, the nonlinear behaviour of a parametrically excited system with electromagnetic excitation is accurately modelled, predicted and experimentally investigated. The equations of motion include both the electromechanical coupling factor and the electromechanical damping. Unlike previous studies where only linear time-varying stiffness due to electromagnetic forces was presented, in this paper the effect of the induced current is studied. As a consequence, nonlinear parameters such as electromechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…MCST This section studies the dynamic behavior of micro-plates under electrostatic excitation by using the modal and the Galerkin method. Among various modes that have been used, it is found that the first one is the predominant mode on the dynamic behavior of micro-plates [78]. To determine the discretized form, by applying the Galerkin method, the solution w in terms of the linear mode shapes is postulated as [79]:…”
Section: Analysis Of Dynamic Behavior Of Micro-plates In Response To mentioning
confidence: 99%
“…MCST This section studies the dynamic behavior of micro-plates under electrostatic excitation by using the modal and the Galerkin method. Among various modes that have been used, it is found that the first one is the predominant mode on the dynamic behavior of micro-plates [78]. To determine the discretized form, by applying the Galerkin method, the solution w in terms of the linear mode shapes is postulated as [79]:…”
Section: Analysis Of Dynamic Behavior Of Micro-plates In Response To mentioning
confidence: 99%
“…Once the structural model is fixed, the nonlinear identification problem is reduced to parameter estimation as only the coefficients of the model terms remain unspecified. The subject of parametric nonlinear identification is extremely broad, and an extensive literature exists (e.g., [6][7][8][9][10]). It is not intended to provide a comprehensive overview of the past and current approaches for the parametric identification of nonlinearity in this paper.…”
Section: Literature Surveymentioning
confidence: 99%
“…The linear natural frequency and the linear mechanical damping ratio are measured from impact tests as ω n = 32.59 rad s −1 and ζ m = 0.001, respectively. More information regarding these measurements can be found in Zaghari (2016). Figure 3 shows the amplitude-frequency relation for step up and down tests, which are carried out by increasing and decreasing the base excitation (shaker) frequency.…”
Section: Nonlinear System With Positive Cubic Stiffnessmentioning
confidence: 99%
“…To generate a current with various phase differences with the acceleration of the shaker, a separate hardware was programmed to generate current with different phase. More details are explained in Zaghari (2016). Figure 4 shows the stable solutions versus phase φ when parametric stiffness is below the instability threshold (δ < δ th ), and when it is above the instability threshold (δ > δ th ) where δ th = 4ζ m .…”
Section: The Effects Of Parametric Stiffness For Varying Phasementioning
confidence: 99%